Comparison of Early Mechanical and Infective Complications in First Time Blind, Bedside, Midline Percutaneous Tenckhoff Catheter Insertion with Ultra-Short Break-in Period in Diabetics and Non-Diabetics: Setting New Standards. Issue 6 (November 2016) - George, Ninoo; Alexander, Suceena; David, Vinoi George; Basu, Gopal; Mohapatra, Anjali; Valson, Anna T.; Jacob, Shibu; Pathak, Harish K.; Devasia, Antony; Tamilarasi, Veerasamy; Varughese, Santosh
Background: There are no large studies that have examined ultra-short break-in period with a blind, bedside, midline approach to Tenckhoff catheter insertion. Methods: Observational cohort study of 245 consecutive adult patients who underwent percutaneous catheter insertion for chronic peritoneal dialysis (PD) at our center from January 2009 to December 2013. There were 132 (53.9%) diabetics and 113 (46.1%) non-diabetics in the cohort. Results: The mean break-in period for the percutaneous group was 2.68 ± 2.6 days. There were significantly more males among the diabetics (103 [78%] vs 66 [58.4%], p = 0.001). Diabetics had a significantly higher body mass index (BMI) (23.9 ± 3.7 kg/m 2 vs 22.2 ± 4 kg/m 2, p < 0.001) and lower serum albumin (33.1 ± 6.3 g/L vs 37 ± 6 g/L, p < 0.001) compared with non-diabetics. Poor catheter outflow was present in 6 (4.5%) diabetics and 16 (14.2%) non-diabetics ( p = 0.009). Catheter migration was also significantly more common in the non-diabetic group (11 [9.7%] vs 2 [1.5%], p = 0.004). Primary catheter non-function was present in 17(15%) of the non-diabetics and in 7(5.3%) of the diabetics ( p = 0.01). There were no mortality or major non-procedural complications during the catheter insertions. Among patients with 1 year of follow-up data, catheter survival (93/102 [91.2%] vs 71/82 [86.6%], p = 0.32) and technique survival (93/102 [91.2%] vs 70/82 [85.4%], p = 0.22) at 1 year was comparable between diabetics and non-diabetics, respectively. Conclusions: Percutaneous catheter insertion by practicing nephrologists provides a short break-in period with very low mechanical and infective complications. Non-diabetic status emerged as a significant risk factor for primary catheter non-function presumed to be due to more patients with lower BMI and thus smaller abdominal cavities. This is the first report that systematically compares diabetic and non-diabetic patients.